Morphometric and phylogenetic analyses of Serpentirhabdias viperidicus n. sp. (Nematoda: Rhabdiasidae) from the lancehead snake Bothrops moojeni Hoge, 1966 (Reptilia: Serpentes: Viperidae) in Brazil - Morais, D. H. [UNESP]; Aguiar, A. [UNESP]; Müller, M. I. [UNESP]; Narciso, R. B. [UNESP]; Da Silva, L. A.F. [UNESP]; Da Silva, R. J. [UNESP] (Cambridge University Press (CUP), 2017)
Serpentirhabdias viperidicus n. sp. (Nematoda: Rhabdiasidae) is described from the lungs of the 'Brazilian lancehead' Bothrops moojeni (Hoge, 1966) from the savannah in São Paulo State, Brazil. The new species is the eighth species of Serpentirhabdias described in the Neotropical region, and differs from other species mainly by a combination of characters: lips slightly notable, presence of fine striations at posterior ends, presence of two parallel lines with intercalated pores, a pore-shaped phasmid situated at the level of the anal aperture and another two in the posterior half of the tail. It is the first species of Serpentirhabdias reported in this snake host and the second species of this genus found parasitizing South American viperidian snakes. Molecular phylogenetic analysis using ribosomal (ITS and 28S partial) genes confirms Serpentirhabdias viperidicus n. sp. as a new species that clustered in the Serpentirhabdias clade, sister taxon to Serpentirhabdias fuscovenosa and Serpentirhabdias elaphe. This is the first description of Serpentirhabdias species from Brazil using molecular approaches and morphological characters to confirm the monophyly of this recent genus.